Factors Affecting Bus Rollover - Zulkipli, Z.H.; Mohd Faudzi, S.A.; Abdul Manap, A.R. (Journal of the Society of Automotive Engineers Malaysia, 2021)
The objectives of this study are to identify factors affecting bus rollover and to study the association between vehicle and environment factors on bus rollover. For analysis, an analytical mathematical model of steady-state vehicle stability for heavy vehicle was used. For the analysis, four parameters were selected namely the super elevation and gradient of road, the track width of the vehicle and the radius of curvature. The design factorial was used to analyse the effect of these four factors to the increase of rollover index. This study has demonstrated the effect of superevelation, gradient, track width of vehicle and radius of curvature to the rollover index of vehicle. It is shown that the most significant factor on rollover index of vehicle is the radius of curvature during manoeuvring.